2015
DOI: 10.18865/ed.25.4.451
|View full text |Cite
|
Sign up to set email alerts
|

Residential Segregation and Diabetes Risk among Latinos

Abstract: <p class="Pa7"><strong>Objective: </strong>To examine whether residence in ethnically segregated metropolitan areas is associated with increased diabetes risk for Latinos in the United States.</p><p class="Pa7"><strong>Methods: </strong>Population data from the 2005 Behavioral Risk Factor Surveillance System and the 2005 American Community Survey were used to determine whether higher levels of Latino-White segregation across metropolitan statistical areas (MSAs) in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The clustering dimension appeared in 7 studies (Bell et al, ; Biello, Ickovics, Niccolai, Lin, & Kershaw, ; Grady, ; Lutfi et al, ; Lutfi et al, ; Walton, ; Yang et al, ), and both the concentration and centralization dimensions were included in four studies (Biello, Ickovics, et al, ; Lutfi et al, ; Lutfi et al, ; Yang et al, ). Six studies used the work by Massey and Denton () to define hypersegregated MSAs as those areas with at least four dimensions that suggested high black/white segregation (Biello, Ickovics, et al, ; Biello, Niccolai, Kershaw, Lin, & Ickovics, ; Grigsby‐Toussaint et al, ; Jones, ; Lutfi et al, ; Osypuk & Acevedo‐Garcia, ). While the segregation measures that take spatial relationships among areal units into account have been used to explore their relationships with health (Bravo et al, ; Debbink & Bader, ; Grady, ; Grady, ; Grady & McLafferty, ; Grady & Ramírez, ; Kramer et al, ; Mayne et al, ; Salow et al, ), most of the segregation indicators in the selected studies presume that the subunits within the main unit of interest are spatially independent.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The clustering dimension appeared in 7 studies (Bell et al, ; Biello, Ickovics, Niccolai, Lin, & Kershaw, ; Grady, ; Lutfi et al, ; Lutfi et al, ; Walton, ; Yang et al, ), and both the concentration and centralization dimensions were included in four studies (Biello, Ickovics, et al, ; Lutfi et al, ; Lutfi et al, ; Yang et al, ). Six studies used the work by Massey and Denton () to define hypersegregated MSAs as those areas with at least four dimensions that suggested high black/white segregation (Biello, Ickovics, et al, ; Biello, Niccolai, Kershaw, Lin, & Ickovics, ; Grigsby‐Toussaint et al, ; Jones, ; Lutfi et al, ; Osypuk & Acevedo‐Garcia, ). While the segregation measures that take spatial relationships among areal units into account have been used to explore their relationships with health (Bravo et al, ; Debbink & Bader, ; Grady, ; Grady, ; Grady & McLafferty, ; Grady & Ramírez, ; Kramer et al, ; Mayne et al, ; Salow et al, ), most of the segregation indicators in the selected studies presume that the subunits within the main unit of interest are spatially independent.…”
Section: Resultsmentioning
confidence: 99%
“…Four of the seven studies that explicitly measured white/Asians segregation found that Asians benefited from high segregation in terms of low risk of having a low birth weight baby and smoking during pregnancy (Walton, ; Yang et al, ), low odds of late‐stage breast cancer diagnosis (Mobley, Kuo, et al, ) and early‐stage breast cancer surgery (Ojinnaka et al, ), and low sodium‐potassium ratio (Yi et al, ). Thirteen studies did not find a significant relationship between racial/ethnic segregation and health disparities (Anderson & Fullerton, ; Biello, Niccolai, et al, ; Britton & Velez, ; Grigsby‐Toussaint et al, ; Haas, Earle, Orav, Brawarsky, Keohane, et al, ; Harvey et al, ; Kershaw et al, ; Kershaw & Albrecht, ; Kovalchik et al, ; Mendez et al, ; Piontak & Schulman, ; Plascak et al, ; Tempalski et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…None have focused upon AI/ANs (Kershaw & Pender, 2016). Most previous studies reported no relationship between racial segregation and diabetes prevalence (Gaskin et al, 2014; Grigsby-Toussaint, Jones, Kubo, & Bradford, 2015; Lim, Yi, Lundy De La Cruz, & Trinh-Shevrin, 2015; Piccolo, Duncan, Pearce, & McKinlay, 2015), but higher segregation was associated with higher diabetes mortality among Blacks (Hunt, Whitman, & Henry, 2014; Rosenstock, Whitman, West, & Balkin, 2014). Such findings imply that greater neighborhood concentration of racial minorities may impact the management, but not necessarily the development, of the disease (Kershaw & Pender, 2016).…”
Section: Discussionmentioning
confidence: 86%
“…The maximum CASP score was 10/10 and all papers scored at least 7/10. Reasons for exclusion included lack of relevance to the title of the review [ 21 ], participants not meeting our inclusion criteria (e.g. studies undertaken in people who did not have an elevated risk of diabetes or pre-diabetes) [ 22 ] and studies that focused exclusively on GDM and the not future risk of diabetes [ 23 ].…”
Section: Resultsmentioning
confidence: 99%